A comparative analysis of updating and balancing methods for social accounting matrices - Traoré, Fousseini; Camara, Alhassane; Fonton, Kike Yra (International Food Policy Research Institute, 2020)
Computable General Equilibrium (CGE) models, which are widely used in the literature to quantify potential impacts of economic public policies, are calibrated on data from Social Accounting Matrices (SAM). SAM belongs to national accounting systems and represents interactions between activities and institutions within an economy. According to Decaluwé & al. (2001) “on one side, a SAM shows a coherent representation of transactions which have taken place within an economy - country, region or a set of countries or regions – while on other side, it provides policy makers with an accounting basis for an analytical framework that can facilitate their choices.” Building a SAM for recent years may, however, be difficult and time-consuming, since it requires accessing, gathering, and compiling data from different sources.2 Furthermore, even if these data are available at the time of building the SAM, they may be obsolete and hence, useless. To overcome this issue, the literature suggests updating existing SAM using the latest information and data about the economy under study (Robinson et al., 2001). Several methods have been employed through the literature, thus paving the way to discussions about their strengths and weaknesses.